Species Distribution Models Reveal Varying Degrees of Refugia From the Invasive Asian Needle Ant for Native Ants Versus Ant‐Plant Seed Dispersal Mutualisms - Drew Kanes; Daniel Malagon; Ben Camper; Anna Hewitt; Simon Dunn; Eva Purcell; Sharon Bewick (Ecology and Evolution)
ABSTRACT The Asian Needle Ant, Brachyponera chinensis (Hymenoptera: Formicidae), has spread throughout a substantial portion of the southeastern United States where it has primarily been restricted to low elevations. We focused on the B. chinensis invasion in Great Smoky Mountains National Park (GSMNP). Records in and near the park represent some of the highest elevation locations of B. chinensis in North America. The goals of this study were to characterize the status of the B. chinensis invasion in GSMNP, to assess the role that disturbance and human visitation play in B. chinensis invasion within GSMNP, to identify the potential of B. chinensis to spread into higher elevations in the park and the southern Appalachians and to determine the impact that this might have on native species, including keystone seed‐dispersers within the Aphaenogaster rudis complex and their myrmecochorous plants. We surveyed GSMNP for B. chinensis at 45 sites, including sites that were burned during the 2016 Gatlinburg fire, sites with high human visitation, and undisturbed sites. We then built species distribution models (SDMs) for B. chinensis and some of the native species that B. chinensis is most likely to impact. This allowed us to assess the potential for high‐elevation refugia within the southern Appalachians. We did not find B. chinensis at any undisturbed sites in GSMNP. We did find B. chinensis at five high‐visitation sites. Field findings were consistent with our SDMs, which suggested that GSMNP's unique precipitation regimes may act as a barrier to invasion. Unfortunately, SDMs indicated moderate suitability for B. chinensis across a sizable proportion of the northern border of the park. This is a region where B. chinensis may have disproportionate impacts on myrmecochorous plant species. Thus, although southern Appalachian precipitation and temperature regimes may provide a refuge from B. chinensis at high elevations, this will not protect all species likely to be impacted by this invasive ant.